Solve: 2(x-1)-3 = -3x +2Originally Posted byold & new

First expand the bracketed term to give:

2x - 2 - 3 = -3x + 2,

which becomes:

2x - 5 = -3x + 2.

Now add 3x to both sides to give:

2x + 3x - 5 = -3x + 3x +2,

which becomes:

5x - 5 = 2.

Now add 5 to both sides:

5x - 5 + 5 = 2 + 5,

which is:

5x = 7.

Now divide both sides by 5 to give:

(5x)/5 = 7/5,

or:

x = 7/5 = 1.4.

Reality check: put x=1.4 in to the LHS of:

2(x-1)-3 = -3x +2

gives:

2(0.4) - 3 = -2.2.

Now put x=1.2 into the RHS gives:

-3*1.4 + 2 = -2.2

which checks out (note in this last expression I have used *

as the multiply symbol to avoid confusion with the decimal point

and x as a variable label).

RonL